Device engineering of p-CuAlO2/β-Ga2O3 interface: A staggered-gap band-alignment - Chowdam Venkata Prasad; Madani Labed; Mohammad Tauquir Alam Shamim Shaikh; Ji Young Min; Tan Hoang Vu Nguyen; Wonjin Song; Jang Hyeok Park; Kyong Jae Kim; Sangmo Kim; Sinsu Kyoung; Nouredine Sengouga; You Seung Rim (Materials Today Advances, 2023)
In this work, by controlling the oxygen flow rate (OFR) (from 0% to 30%), we suggest using a p-type copper aluminum oxide (p-CuAlO2) interlayer to enhance the high breakdown and low leakage current for β-Ga2O3-based power device applications. Results of AFM measurements on p-CuAlO2 films performed using various OFRs demonstrate that greater OFRs result in an increase in film roughness payable to the unavoidable leading of defects/oxygen vacancy (VO). We used XPS and TEM analysis to validate the surface elemental compositions, chemical states, band offsets and microstructural properties of p-CuAlO2/β-Ga2O3 heterojunction (HJ) with different OFRs. With increasing OFR from 0% to 17.6%, the VBO and CBO values of HJ were decreased from 1.73 eV to 1.23 eV and from 0.53 eV to 0.38 eV respectively. Then, with increasing OFR from 17.6% to 30%, VBO was decreased from 1.23 eV to 1.13 eV while CBO increased from 0.38 eV to 0.58 eV. The staggered-gap (type-II) across the p-CuAlO2/β-Ga2O3 HJ is identified the entire OFRs. The rising tendency of optical bandgap (Eg) of p-CuAlO2 with range of OFRs, a maximum Eg of 4.35 eV was obtained with OFR of 30%. Furthermore, the electrical and carrier transport properties of p-CuAlO2/β-Ga2O3 HJ were studied using I–V and C–V techniques. The reverse breakdown voltage (Vbr) of HJ is strongly dependent on OFRs. With increasing OFRs, Vbr was decreased from 937 V to 924 V, and then to 1000 V with increasing OFR from 0% to 17.6% and then to 30%. In addition, a decrease in the interface state density (NSS) with increasing OFRs was observed which indicates that oxygen may be an effective surface passivation. Analysis confirmed that Poole-Frenkel emission dominates the reverse leakage current of all the HJ samples. The type-II p-CuAlO2/β-Ga2O3 HJ may facilitate the design and manufacture of high-performance β-Ga2O3-based heterojunctions and advance optoelectronic devices.